Problem- Based Learning for Determination of Fitness for Work and Return to Work - Seyedeh Negar Assadi (Tabriz University of Medical Sciences, 2016)
Background: Learning about fitness for work and return to work is an important subject for students in the medical sciences, but the educational method is important too. Problem-based learning (PBL) is an important method that should be examined in occupational health studies. The objective of this study was to compare the effects of three educational methods for learning about fitness for work and return to work for students in the medical sciences. Methods: This study was a quasi-experimental study using the curriculum of the Ministry of Health for 150 occupational health students in the School of Health at Mashhad University; fitness for work and return to work was taught with attention to various educational methods. Group A (n = 50) received presentations and lectures; group B (n = 50) received additional Clinical practice observations; and group C (n = 50) received PBL. Pre- and post-assessments were used to determine change in knowledge and the results were compared among the three groups of participants; then results of exams were analyzed with SPSS 16, using Analysis of variance (ANOVA) (with post hoc Tukey), and statistical significance of P < 0.05. Results: The total grade (20) of fitness for work and return to work for group A was 13.22 ± 0.64, for group B, 14.27 ± 1.01 and for group C, 16.28 ± 0.01. The between-groups comparisons showed significant differences among all three groups (P < 0.001). The level of learning - change in knowledge - among the three groups was also significant, with P < 0.001. The odds ratio was 1.44 (1.12-3.24) for group C with PBL. Conclusion: According to the results, PBL was the best method for learning of fitness for work and return to work in students studying medical sciences.